Might patients with cerebellar ataxia benefit from the Computer Assisted Rehabilitation ENvironment (CAREN)? A pilot study focusing on gait and balance - Bonanno, Mirjam; De Pasquale, Paolo; De Marchis, Cristiano; Lombardo Facciale, Antonino; Paladina, Giuseppe; Fonti, Bartolo; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Bioengineering and Biotechnology, 2024)
Ataxia is a neurological symptom that causes decreased balance, loss of coordination, and gait alterations.Innovative rehabilitation devices like virtual reality (VR) systems can provide task-oriented, repetitive and intensive training with multisensorial feedback, thus promoting neuroplastic processes. Among these VR technologies, the Computer Assisted Rehabilitation ENvironment (CAREN) associates a split belt treadmill on a 6-degrees of freedom platform with a 180° VR screen and a Vicon motion capture system to monitor patients' movements during training sessions. Eight patients affected by cerebellar ataxia were enrolled and received 20 sessions of CAREN training in addition to standard rehabilitation treatment. Each patient was evaluated at the beginning and at the end of the study with 3D gait analysis and clinical scales to assess balance, gait function and risk of falls. We found improvements in kinematic, kinetic, and electromyographic parameters (as per prepost-CAREN training), as well as in clinical outcomes, such as balance and risk of falls in ataxic patients. In addition, we found that trunk rotation improved, after CAREN intervention, approximating to the normative values. Our results suggested that CAREN might be useful to improve specific biomechanical parameters of gait in ataxic patients.